STUDI RECTENNA (RECTIFIER ANTENNA) UNTUK MENGUBAH GELOMBANG ELEKTROMAGNETIK RF MENJADI SUMBER TEGANGAN DC - Nurhady Mustofa; Jatmiko Endro Suseno (Youngster Physics Journal, 2016)
RF (Radio Frequency) electromagnetic waves energy source  are still very rare utilization besides using the RF signal is very much especially in the areas of technology and telecommunications, resulting in the number of RF electromagnetic energy in the air, if the energy source of the RF electromagnetic wave can be utilized as a DC voltage source will be promising alternative energy sources and environmentally friendly. Simulations conducted to determine the ability of the rectifier circuit, then design a rectifier that can work on GSM frequencies and antennas used Quad Band 850/900/1800/1900 antenna ANT-GXH915. Tests conducted two places, namely the testing performance of rectifier and environmental testing. Results of testing performance of rectifier using the Signal Generator at a frequency range of 50 MHz - 900 MHz rated voltage of 1,56 volts and a current of 35 uA with an efficiency of 13,95%. The results of environmental testing conducted by two sources that the source of the cellular telephone and the BTS source. Results from the source mobile phone when making calls obtained voltage value of 1,54 Volt and a current of 0,25 mA at a distance of 1 cm. Results from the source BTS to a distance of 37 meters obtained voltage value of 0,405 Volt.Keywords: rectenna, antena, rectifier, energy harvesting.